Creation, Innovation, Technology and Research Exposition (CITREx 2013), March 27-28, 2013 Universiti Malaysia Pahang (UMP) Sports Complex - Noor Syahidah, Sabran (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP) displayed 179 of its research works at the Creation, Innovation, Technology and Research Exposition or CITREx 2013 that was held at its Sports Complex on March 27-28, 2013.